Investigating Inventory Strategy Under Demand Distribution Fluctuation in Dual-Channel Supply Chain - Xu, Nai-Ru; Cheng, Jie; Cai, Zheng-Qun (Frontiers in Physics, 2021)
The manufacturers need to solve the inventory management problem existing in the dual channel so as to ensure supply to the dual channel and reduce the inventory cost of supply chain system when they construct a dual channel distribution system including online sale channel and offline sale channel. The dual channel supply chain is the research object, and the inventory decision model is designed to achieve optimal profit in the condition that the market demand is divided into online demand and offline demand, the numerical analysis and simulation is made by means of MATLAB for the model, the simulation results indicate that manufacturers and retailers both increase inventory and their profits decrease when demand uncertainty increases. Besides, the increase of online demand ratio will cause that manufacturers’ inventory and profit increase and the profit of retailers and the whole supply chain decrease.